Global and Specific Profiles of Executive Functioning in Prodromal and Early Psychosis - Hwang, Wu Jeong; Lee, Tae Young; Shin, Won-Gyo; Kim, Minah; Kim, Jihyang; Lee, Junhee; Kwon, Jun Soo (Frontiers in Psychiatry, 2019)
Objective: Numerous reports on neurocognitive functioning deficits in individuals at clinical high risk (CHR) and first-episode psychosis (FEP) patients suggest particular deficits in executive functioning (EF). However, to date, most of the studies have administered a single or a few EF tests to participants, and few investigations have examined the different components of EF to identify specific subdomains of relative strength and weakness. Method: Forty CHR subjects, 85 FEP patients and 85 healthy controls (HC) were assessed with a neuropsychological battery to elucidate the profiles of EF in the subdomains of shift, attention, fluency, and planning. Results: In the subdomains of shift, attention and fluency, CHR individuals and FEP patients showed deficits compared to HC. The post hoc analysis revealed that CHR individuals had preserved attention shifting and phonemic fluency compared to FEP. CHR showed intermediate deficits between FEP and HCs in spatial working memory and semantic fluency, and the largest effect size was observed in semantic fluency both for CHR and FEP. Conclusion: Overall, the findings of this study, in addition to providing detailed profiles of EF in prodromal and early psychosis patients, highlight the informative value of the specific subdomains of semantic fluency and spatial working memory.